Analiza empiryczna zróżnicowania rezultatów pracy ankieterów w kontekście konstrukcji systemu premiowania - Woźniak, Halina; Stańczyk, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The introduction of an additional financial incentive for statistical interviewers aims to improve the quality of statistical surveys carried out in households as well as the quality of quotation of goodsand services conducted in retail outlets and service points, inter alia, by increasing the completeness of these surveys. These are conducted by Statistics Poland and its local agendas, i.e. statistical offices. The aim of the article is to analyse the diversity of results of interviewers’ work in the context of construction of the bonus system. As a measure of the result of the interviewerʼs work, the survey completeness index was used, which may be the basis for the level of thresholds defining the amount of the bonus.
Keywords: survey quality; data quality; survey completeness index; statistical interviewer; bonus system